Mass Spectrometry of Organic Compounds Part I. Oxygenated Quinolines and Furoquinoline Alkaloids Part II. Lobinaline and its Hofmann Degradation Products - Clugston, Donald Maurice (My University, 1966)
Part I The mass spectra of the seven isomeric monomethoxyquinolines, the seven monohydroxyquinolines, the two N-methylquinolones and six furoquinoline alkaloids have been recorded. Fragmentation mechanisms are proposed to account for the major peaks in all the spectra. Use has been made of intense metastable peaks found in most of the spectra to aid the interpretation of the fragmentation routes. In addition, deuterium and carbon-13 labelling have been employed in analyzing the fragmentation routes of the methoxyquinolines.
Part II The Hofmann degradation of lobinaline is described. Examination of lobinaline, its derivatives and its Hofmann degradation products by mass spectrometry and other physical and chemical techniques has allowed a structure to be assigned to the alkaloid.
Keywords: spectra, furoquinoline, alkaloids, lobinaline, oxygenated